Efficient conversion of orbital Hall current to spin current for spin-orbit torque switching - Lee, Soogil; Kang, Min-Gu; Go, Dongwook; Kim, Dohyoung; Kang, Jun-Ho; Lee, Taekhyeon; Lee, Geun-Hee; Kang, Jaimin; Lee, Nyun Jong; Mokrousov, Yuriy; Kim, Sanghoon; Kim, Kab-Jin; et al. (Communications Physics, 2021)
Spin Hall effect, an electric generation of spin current, allows for efficient control of magnetization. Recent theory revealed that orbital Hall effect creates orbital current, which can be much larger than spin-Hall-induced spin current. However, orbital current cannot directly exert a torque on a ferromagnet, requiring a conversion process from orbital current to spin current. Here, we report two effective methods of the conversion through spin-orbit coupling engineering, which allows us to unambiguously demonstrate orbital-current-induced spin torque, or orbital Hall torque. We find that orbital Hall torque is greatly enhanced by introducing either a rare-earth ferromagnet Gd or a Pt interfacial layer with strong spin-orbit coupling in Cr/ferromagnet structures, indicating that the orbital current generated in Cr is efficiently converted into spin current in the Gd or Pt layer. Our results offer a pathway to utilize the orbital current to further enhance the magnetization switching efficiency in spin-orbit-torque-based spintronic devices.
CRIS-Team Scopus Importer:2023-03-27